2019
DOI: 10.1017/s0144686x19001740
|View full text |Cite
|
Sign up to set email alerts
|

Comparing socio-economic inequalities in healthy ageing in the United States of America, England, China and Japan: evidence from four longitudinal studies of ageing

Abstract: Healthy ageing has become a popular topic worldwide. So far, a consensus measure of healthy ageing has not been reached; and no studies have compared the magnitude of socio-economic inequality in healthy ageing outside Europe. This study aims to create a universal measure of healthy ageing and compare socio-economic inequalities in healthy ageing in the United States of America (USA), England, China and Japan. We included 10,305 American, 6,590 English, 5,930 Chinese and 1,935 Japanese participants for longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…The early detection of HL by primary care professionals in routine assessments could help prevent or delay the onset of depression, particularly in lower wealth groups. Untreated HL may not only have negative consequences for people's functional ability and mental wellbeing, but also to society as a whole, as our paper showed that HL may widen the socioeconomic inequalities through its graded impact on people's wealth [42]. Taking SEP into account is considered an essential element of depression prevention strategies in the general population [43].…”
Section: Discussionmentioning
confidence: 84%
“…The early detection of HL by primary care professionals in routine assessments could help prevent or delay the onset of depression, particularly in lower wealth groups. Untreated HL may not only have negative consequences for people's functional ability and mental wellbeing, but also to society as a whole, as our paper showed that HL may widen the socioeconomic inequalities through its graded impact on people's wealth [42]. Taking SEP into account is considered an essential element of depression prevention strategies in the general population [43].…”
Section: Discussionmentioning
confidence: 84%
“…On the one hand, fundamental cause theory suggests those with high education levels may choose to live in advantaged neighborhoods [ 20 ]. On the other hand, some participants in the first or second survey died and therefore did not reply to the subsequent surveys [ 14 ]. As such, cohort weight was applied to reduce the bias.…”
Section: Discussionmentioning
confidence: 99%
“…As People's Republic of China was founded in 1949, the illiteracy rate is as high as 80%. In 1950, the Chinese government promoted literacy education nationwide to gradually reduce illiteracy [ 14 ]. The standard of literacy education is to have preliminary reading, writing, and arithmetic skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A person's participation in education is still affected by social inequalities; this also holds true in old age after retirement (Bjursell et al, 2017;Boeren, 2017). The intersection between age and inequalities can lead to even more severe constraints regarding one's capabilities (Heap et al, 2017;Lu et al, 2019). From semester fees to public transportation, some costs are involved, and these costs can affect older people differently depending on their financial situation.…”
Section: Theoretical Framework For Motivations and Learning In The Lamentioning
confidence: 99%